2012
DOI: 10.1128/cvi.05443-11
|View full text |Cite
|
Sign up to set email alerts
|

Antibody in Middle Ear Fluid of Children Originates Predominantly from Sera and Nasopharyngeal Secretions

Abstract: The human middle ear is devoid of any immunocompetent cells in normal mucosa. We sought to determine the source of antibody present in the middle ear of children. Total IgG, IgA, and secretory IgA antibodies were determined by enzyme-linked immunosorbent assay from the nasopharyngeal, middle ear, and serum samples of children with acute otitis media. The two-dimensional gel electrophoresis pattern of the entire array of IgA antibodies in the nasal wash (NW) and middle ear fluid (MEF) was compared from the MEF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The NP mucosal compartment cytokine levels diverged from the responses in the peripheral blood, but were similar to those in the middle ear. These data are consistent with our earlier report [16] that MEF contains predominantly secretions from the NP, and suggests limited migration of immune cells or transudation of immune effectors from blood. IL-2 production plays a significant role in driving inflammatory responses during experimental AOM infection of animal models [28][29][30].…”
Section: Il-17asupporting
confidence: 93%
“…The NP mucosal compartment cytokine levels diverged from the responses in the peripheral blood, but were similar to those in the middle ear. These data are consistent with our earlier report [16] that MEF contains predominantly secretions from the NP, and suggests limited migration of immune cells or transudation of immune effectors from blood. IL-2 production plays a significant role in driving inflammatory responses during experimental AOM infection of animal models [28][29][30].…”
Section: Il-17asupporting
confidence: 93%
“…Conversely, our hypothesis is that otopathogen-specific T-cell memory, if generated, primarily is effective in immune protection by activity in the nasopharynx and the Eustachian tube, with most cells originating from regional lymph nodes, i.e., the tonsils and adenoids. In support of that notion we have shown that the antibody present in middle ear fluid predominantly, if not exclusively, derives from the serum by transudation and reflux of antibody produced in the nasopharynx that reaches the middle ear by way of the Eustachian tube[28] and that MEF of children with AOM is largely devoid of lymphocytes (unpublished).…”
Section: Introductionmentioning
confidence: 72%
“…T-, B- cells, macrophages, dendritic cells and natural killer (NK) cells) and antibodies into the MEF and middle ear mucosa after the onset of AOM [28, 53, 55, 56]. T-cells were described as dominant among the lymphocytes in the MEF during AOM, with CD4 + CD45RO + memory T-cells predominating[53].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that the IgG:IgA ratio in MEF resembled that observed in serum but that small amounts of SIgA were also detected (Kaur et al, 2012).…”
Section: Secretory Immunoglobulin a In The Middle Earmentioning
confidence: 77%